Using eXtended Reality as Digital Twin for Training and Collaboration: the FLEX-XR case study - Thijssen, D.; Petermeijer, S.M.; Nabben, A.C. (National Training & Simulation Association, 2022)
More than fifty years ago man first set foot on the moon, followed by six more successful crewed missions to the lunar surface. The last crewed mission dates back to 1972, after which interest in moon exploration diminished. Renewed interest in lunar exploration and colonization sparked the development of the Lunar analogue facilities (LUNA) at the ESA’s Astronaut Centre (EAC) in Cologne. Part of LUNA is the Future Lunar Exploration Habitat (FLEXHab), which will serve as a simulation habitat to train for future lunar missions. In order to maximize efficiency and flexibility in the use of FLEXHab, the user should be able to familiarize themselves with the simulation before entering or during the utilisation of the facility. Extended Reality (XR) is expected to provide these benefits with a low-cost solution. The FLEX-XR project goal is to showcase possibilities of Virtual Reality for user familiarisation with the FLEXHab facilities, as well as support them in their experiment design process, by creating a digital twin of the facility and some of the intended experiments. This digital twin will consist of a Virtual Reality (VR) application allowing users to prepare for their experiments (e.g. laboratory lay-out, required instruments and wiring) and to train as a group, with a focus on familiarizing these users with the facility. At a later stage, an Augmented Reality (AR) application will also be developed to offer just-in-time and just-in-place information, procedures and data streams, while working in the real FLEXHab. Cooperation with ground support can also be facilitated by this AR application. FLEX-XR aims to demonstrate the added value of VR- and AR-applications for future lunar missions.